Efficacy and safety of sequential immunosuppressive treatment for severe IgA nephropathy: A retrospective study - Luo, Mian-Na; Pan, Qingjun; Ye, Ting; Li, Shangmei; Yang, Lawei; Liu, Hua-Feng; Xu, Yongzhi (Frontiers in Pharmacology, 2023)
Background: This study comparedthe efficacy and safety of sequential immunosuppressive therapy in patients with non-end-stage IgA nephropathy (IgAN) with Lee's classification of IV V and provided evidence for the use of immunotherapy in patients with severe IgAN. Methods: We retrospectively analyzed theclinical data of patients with Lee's IV V non-end-stage IgA nephropathy. Results: 436 patientswere diagnosed with IgAN, and 98patients who met the inclusion criteriawere included in this retrospective study. Ofthese, 17 were in the supportive care group, 20 in the P group (prednisone-only), 35 in P+CTX group (the prednisone combined with cyclophosphamide followed by mycophenolate mofetil), and 26 in the P+MMF group (prednisone combined with mycophenolate mofetil). The four groups showed differences in the segmental glomerulosclerosis score and the proportion of patients with Lee's grade IV (P<0.05), but no differences in other indicators. Compared with the baseline values, urine protein-to-creatinine ratio (PCR)significantly decreased and serum albumin increased (P<0.05), but there was no significant difference between the groups. Theestimated Glomerular Filtration Rate (eGFR) of the P, P+MMF, and P+CTX groups was higher than that of the supportive care group at the 6th and 24th month after treatment (all P<0.05). At the 24th month, the eGFRin the P+CTX group was higher than that in the P+MMF group (P<0.05). The effective remission rate of the P+CTX group was higher than that of the supportive care group (P<0.05). At 12 months, the effective remission rate of the P group was higher than that of the supportive care group (P<0.05). At the 24th month, there was no significantdifference in the effective remission rates among the three groups (P, P+MMF, and P+CTX). 9 patients with severe IgA nephropathy reached the endpoint. Conclusion: This studyshowed that immunosuppressive therapy insevere IgANpatientscan effectively reduceurinary protein, increase albumin, and protect renal function in the early stages of IgAN.P+CTXis the most commonly used, which has a high effective remission rate of urine protein and a low incidence of end-point events.